Pengaruh Pelatihan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Studi Kasus Primkoppabri Cabang Brebes - Salsabila Ramadhani; Azizah Indriyani; Roby Setiadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study has the main objective, namely to find out how the effect of job training and work motivation on employee performance at the Primkoppabri branch of Brebes. This research uses quantitative research with the SPSS 22 analysis tool. The population used in this research is Primkoppabri employees, totaling 74 employees. The sample in this study uses a saturated sample where all the number of employees is used in the sample. The method of data collection is done by distributing questionnaires. The results of the t test show that the job training variable has a significant positive effect on employee performance with a t count > t table (2.618 > 1.993) and a sig value of 0.011 <0.05. The variable of work motivation has a significant positive effect on employee performance with a t count > t table (6.428 > 1.993) and a sig value of 0.00 <0.05. Then through the F test it is known that the variables of job training and work motivation simultaneously influence employee performance with F count > F table (84.066 > 2.50). Adjuster R square of 70.4% indicates that job training and work motivation variables affect employee performance, and the rest is influenced by other variables.